Kearifan Lokal untuk Membangun Perdamaian (Sebuah Analisis terhadap Tafsīr al-Bayān karya Shodiq Hamzah) - Zaman, M. Badruz; Mawardi, Imam; Muna, Muhammad Yusril (Jurnal Lektur Keagamaan, 2024)
This study examines the values of local wisdom in Tafsīr al-Bayān by Shodiq Hamzah and its role in promoting peace through tolerance, respect for traditions, and non-violence. Written in Javanese using Latin script while preserving the pesantren Pegon tradition, this work reflects a synthesis of Islamic scholarship and local culture. Employing qualitative library research, the study uses the concept of local wisdom as a framework for peacebuilding within religious moderation. A thematic approach identifies and analyzes Qur’anic verses on peace, interpreted through Shodiq Hamzah’s perspective. The findings reveal that Shodiq Hamzah integrates values like compassion, justice, and wisdom into social interactions while advocating for moderate religious reasoning. His interpretation underscores the importance of local wisdom in resolving interfaith conflicts and fostering harmony. This research enriches the literature by illustrating how religious moderation rooted in local traditions provides a sustainable framework for addressing societal challenges. Tafsīr al-Bayān bridges textual interpretation with cultural context, highlighting the dynamic interplay of Islamic teachings, local wisdom, and contemporary issues, making it a key reference in studies on peace and religious moderation.